Cookies Tinggi Serat Berbahan Ampas Tahu dan Kulit Pisang Raja - Terati Terati; Andini Putri Pertiwi; Anggun Taristi; Ni Shafa Khalishah SR; Riska Septiana (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2023)
One of the nutritional problems that often occurs in children is overweight or obesity. Obesity is a condition where the intake of energy and fat causes the risk of being overweight is higher than the energy expended. The purpose of this study was to determine the acceptability and nutritional content of cookies, tofu pulp flour and plantain peel flour. Tofu pulp is generally used as animal feed because it has low economic value, while plantain peel is the outer part of bananas which are quite widely found. In general, the use of banana peels is still not widely done because it is usually directly disposed of as organic waste or can also be used for animal feed. Experimental research with a non-factorial, Completely Randomized Design (CRD) consisting of four treatments and three repetitions. The results of the acceptability test showed that the most preferred formula was formula 3. The results of laboratory tests on Formula 3 obtained an energy value of 492.66 kcal, 4.76 grams of protein, 24.22 grams of fat, 63.91 grams of carbohydrates, and dietary fiber. 31.18 grams. It was concluded that Formula 3 had the highest acceptability (3.88) and good nutritional value.